Case study: Co-creating a flipped feed-in approach to a virtual biochemistry lab assessment: increasing student achievement and engagement in a large, diverse cohort. Issue 1 (29th April 2022) - Cassambai, Shabana; Bridge, Hannah; Gill, Palak K.; Shobaloju, Similoluwa; Sgamma, Tiziana; Rushworth, Jo V.
Abstract: More inclusive, authentic assessments are required to address awarding gaps and to ensure that bioscience students can apply their knowledge to relevant work-based scenarios. In this case report, we present a co-created approach to designing a more inclusive, virtual biochemistry lab assessment for a diverse cohort of ∼270 first-year students. The assignment was to write up an inclusive clinical case study as a one-page journal article. A flipped classroom approach taught the relevant skills, along with simulated labs from Learning Science Ltd. Student Lecturers co-created the assessment, including the marking rubric and the unexemplars. We replaced traditional feedback with a flipped, feed-in approach where students were able to engage in a formative assessment with peer marking and unexemplars. Whilst the summative assessment was marked anonymously, a dialogue-based approach was employed, where students could request personalised audio feed-forward from the tutor. The high pass rate (97%) and student satisfaction score (88%) suggest that this approach is an effective way to challenge, engage and support a large, diverse cohort of students. First-year students who participated in the flipped feed-in experience obtained a significantly higher summative mark (56.7% cf. 50.9%) than those who did not. Interestingly, students in receipt of learning adjustments scored higher marks on average in the summative assessment (59.3% cf. 54.3%), suggesting that we have reversed the disability-based attainment gap. Further investigation into whether a co-created, flipped feed-in approach can reduce attainment gaps based on ethnicity, gender and age is warranted.